Within-person reproducibility of proteoforms related to inflammation and renal dysfunction - Jie Gao; Adrian McCann; Johnny Laupsa-Borge; Ottar Nygård; Per Magne Ueland; Klaus Meyer (Scientific Reports, 2022)
Abstract Protein biomarkers and microheterogeneity have attracted increasing attention in epidemiological and clinical research. Knowledge of within-person reproducibility over time is paramount to determine whether a single measurement accurately reflects an individual’s long-term exposure. Yet, research investigating within-person reproducibility for proteoforms is limited. We investigated the reproducibility of the inflammatory markers C-reactive protein (CRP), serum amyloid A (SAA), and calprotectin (S100A8/9), and the renal function marker cystatin C (CnC) using a novel immuno-MALDI-TOF MS assay. Reproducibility, expressed as intraclass correlation coefficient (ICC), was calculated for 16 proteoforms using plasma samples of the Western Norway B Vitamin Intervention Trial (WENBIT) cohort collected 1–3 y apart from 295 stable angina pectoris (SAP) patients and 16 weeks apart from 38 subjects of the Intervention with Omega Fatty Acids in High-risk Patients with Hypertriglyceridemic Waist (OMEGA) trial with abdominal obesity but no other documented co-morbidities. ICCs for inflammatory markers were lower in WENBIT (CRP: 0.51, SAAt: 0.38, S100At: 0.31) compared to OMEGA subjects (CRP: 0.71, SAAt: 0.73, S100At: 0.48), while comparable for CnCt (WENBIT: 0.69, OMEGA: 0.67). Excluding SAP patients with elevated inflammation (CRP > 10 µg/ml) increased the ICC of SAAt to 0.55. Reduction of the time interval from 3 to 1 y in WENBIT group increased ICCs for all proteoforms. With a few exceptions ICCs did not differ between proteoforms of the same biomarker. ICCs were highest in OMEGA subjects with fair-to-good reproducibility for all markers. Reproducibility of SAA and S100A8/9 proteoforms in the WENBIT cohort was related to inflammation. This work will inform future clinical and epidemiological research which relies on single time point biomarker assessment to investigate inflammation and renal function.